2021
DOI: 10.3389/fmolb.2021.720645
|View full text |Cite
|
Sign up to set email alerts
|

ARHGAP11A Is a Prognostic Biomarker and Correlated With Immune Infiltrates in Gastric Cancer

Abstract: Background: ARHGAP11A, belongs to RhoGAPs family, is vital for cell motility. However, the role of ARHGAP11A in gastric cancer is obscure.Methods: The expression level of ARHGAP11A was analyzed by Oncomine database. The correlation of ARHGAP11A expression with immune infiltrates and associated gene markers was clarified by Tumor IMmune Estimation Resource and Gene Expression Profiling Interactive Analysis database. The correlation between ARHGAP11A expression and the patient prognosis was identified by Kaplan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…ARHGAP11A, a prognostic biomarker, is correlated with immune infiltrates in gastric cancer. In addition, high ARHGAP11A expression significantly correlated with a better prognosis in gastric cancer (41). However, the role of ARHGAP11A in glioma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…ARHGAP11A, a prognostic biomarker, is correlated with immune infiltrates in gastric cancer. In addition, high ARHGAP11A expression significantly correlated with a better prognosis in gastric cancer (41). However, the role of ARHGAP11A in glioma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The Arhgap11a is a protein-coding gene that locates on chr15q13.3, encoding a member of GTPaseactivating proteins (RhoGAPs), which are upstream regulators of Rho GTPases. The Rho GTPases are a subfamily of the Ras superfamily proteins, which play central roles in multiple biological processes, such as cell motility, cell polarity, cell cycle progression, cell adhesion, migration, and invasion (47). Our study firstly demonstrated targeted inhibition of Arhgap11a by miR-211-facilitated osteogenic differentiation of MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 69%
“…Journal Pre-proof kinase 2 beta (CSNK2B) and HRAS proto-oncogene, GTPase (HRAS) (Supplementary Figure 2 and supplementary Table 2). ARHGAP11A is reported to be overexpressed in a variety of tumours and to play an important role in the proliferation, invasion, metastasis, and cell cycle regulation of tumour cells [24]. SMEK1 overexpression was associated with a 2.8-fold decrease CSNK2B, the regulatory subunit of the serine/threonine protein kinase Casein kinase 2 whose activity is associated with apoptosis suppression [25,26].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%